Dietary patterns as predictors of adverse antidiabetics reactions - A cross-sectional study of polish diabetes sufferers - Skoczylas, Kornelia; Babiarczyk, Beata; Michalik, Anna (Journal of Education, Health and Sport, 2024)
Background: Diabetes mellitus (DM) is a multifaceted problem. There is a need to coordinate the diet with pharmacological interventions, because of the possible interaction between the two. The present study aimed to identify the factors related to the dietary habits of people suffering with diabetes that may increase the risk of adverse reactions to anti-diabetic medication. Methods: Between 2019 and 2020, patients with DM (N=203), aged 18-65, were enrolled for analysis. A quantitative and cross-sectional survey was applied. The study employed a Dietary Habits and Nutrition Beliefs Questionnaire devised in Poland for people aged 15–65 years (KomPAN) and a self-designed questionnaire as research tools. Results: The majority of the patients with DM studied confirmed the use of a low carbohydrate diet in relation to their disease (87.7%). The mean pHDI-10 score for the study group was 22.55±8.67 points and the mean nHDI-14 score was 15.00±9.88 points. The place of residence, education and general financial situation of the subjects had a statistically significant effect on the results (p<0.05). The majority of subjects reported regular use of anti-diabetic medication (77.8%). Of those treated with oral medication, 61.1% had experienced adverse effects and 49.3% had been hospitalized as a result. Of those treated with insulin, 40.9% reported adverse effects. Conclusions: Health professionals should be proactive in giving people with DM, particularly those who are less educated, financially disadvantaged, aged 41-55 and are working, adequate counseling about dietary recommendations from the very onset of their illness.